1997
DOI: 10.1902/jop.1997.68.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin and Cyclosporine A Specifically Regulate Macrophage Phenotype and Expression of Platelet‐Derived Growth Factor and Interleukin‐1 In Vitro and In Vivo: Possible Molecular Mechanism of Drug‐Induced Gingival Hyperplasia

Abstract: Phenytoin (pht) is an anticonvulsant drug commonly used for the prevention of seizures. A common side effect of PHT therapy is gingival hyperplasia, occasionally so severe that it requires surgical intervention. Cyclosporine A (CSA) is a drug widely used for the control of rejection phenomena following solid organ and bone marrow transplantation. A frequent side effect of CSA administration is gingival overgrowth. As yet, the molecular mechanisms of drug-induced gingival hyperplasia are unknown although it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 1 publication
3
74
1
1
Order By: Relevance
“…35 The present study showed elevated expression of CD163 in group II compared to groups III and IV. This is in accordance with Dill et al 36 and Iacopino et al 6 as they concluded that PNT, CsA, and nifedipine GO tissues contain subpopulations of macrophages and other inflammatory cells. These cells differ from those in healthy control gingival tissues.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…35 The present study showed elevated expression of CD163 in group II compared to groups III and IV. This is in accordance with Dill et al 36 and Iacopino et al 6 as they concluded that PNT, CsA, and nifedipine GO tissues contain subpopulations of macrophages and other inflammatory cells. These cells differ from those in healthy control gingival tissues.…”
Section: Discussionsupporting
confidence: 91%
“…2,3 The incidence of this side effect can be as high as 70% in transplant patients, 65% in epileptics, and 30% in hypertensive patients. 4,5 In 1997, Iacopino et al 6 reported that the clinical presentation of inflamed and hyperplastic gingival tissues are associated with specific macrophage phenotypes which express the essential platelet derived growth factor-beta (PDGF-B) in PNT-induced hyperplastic tissues. In contrary, Wright et al concluded that macrophage-derived PDGF B plays a negligible pivotal role in the pathogenesis of DIGO.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, we speculate that EMT in nifedipine-and cyclosporine A-induced gingival overgrowth may be driven by elevated levels of growth factors other than TGF-␤ (such as PDGF) that have been reported to be elevated in gingival overgrowth. 39 TGF-␤1 increases SLUG levels in EMT directly through SMAD-3 signaling.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are of great interest, and suggest that substances that cause gingival overgrowth may do so by altering the normal balance of cytokines in gingival tissues. Cytokines and growth factors found at elevated levels in human drug-induced gingival overgrowth include interleukin-6 (IL-6), IL-1␤, platelet-derived growth factor-B (PDGF-B), fibroblast growth factor-2 (FGF-2), transforming growth factor-␤ (TGF-␤), and connective tissue growth factor (CTGF) (Williamson et al, 1994;Nares et al, 1996;Plemons et al, 1996;Saito et al, 1996;Dill and Iacopino, 1997;Iacopino et al, 1997;Atilla and Kutukculer, 1998;Sasaki and Maita, 1998;Hong et al, 1999;Myrillas et al, 1999;Buduneli et al, 2001;Uzel et al, 2001).…”
Section: Cytokines and Drug-induced Gingival Overgrowthmentioning
confidence: 99%
“…In contrast, macrophages in highly inflamed tissues express predominantly the 27E10 marker . Even though IL-1␤ levels have not been shown to be increased in cyclosporin-A-treated monocytes/macrophages, there was a significant up-regulation in PDGF-B in response to cyclosporin A and phenytoin (Plemons et al, 1996;Iacopino et al, 1997). Similarly, phenytoin, cyclosporin A, and nifedipine gingival overgrowth tissues contain subpopulations of macrophages and other inflammatory cells that differ from those in healthy control gingival tissues (Dahllof et al, 1985;Pernu et al, 1994;Cebeci et al, 1996Cebeci et al, , 1998Pernu and Knuuttila, 2001;Bulut et al, 2002;Echelard et al, 2002).…”
Section: Origins Of Altered Cytokine Balancesmentioning
confidence: 99%